Austria : Report on Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2009)
The paper presents a report on Austria's Observance of Standards and Codes for Financial Action Task Force Recommendations for Antimoney Laundering (AML)/Combating the Financing of Terrorism (AML/CFT). The Austrian authorities have designed and are implementing a comprehensive AML/CFT system, supported by well-developed federal administrative and supervisory bodies, and active professional organizations. The supervisory system for financial institutions is generally sound and efficient. Licensing requirements and the regime of sanctions need to be strengthened, and additional resources should be allocated to supervisory bodies.